Faktor Sikap dan Perilaku yang Berhubungan dengan Malaria di Wilayah Kerja Puskesmas Banjarmangu I Banjarnegara - Zulaikhah Thomas Siti; Menik Sahariyani; Prasetyo Bhakti H; David Akbar M; Mustika Rani (Disease Prevention and Public Health Journal, 2020)
Background: Malaria is an infectious disease caused by Plasmodium and transmitted to humans through the bite of infected female Anopheles. Characteristics of a person affecting the pattern of life that can contribute to the occurrence, attitudes and behaviors that is less attention to environmental  related to Anopheles population can contribute to the malaria. In Indonesia, malaria is found in almost all regions. Some provinces are still malaria endemic areas, both low, medium and high. The number of malaria-based illnesses in API in Central Java in 2014 was recorded at 0.05 per 1000 population, and indigenous cases were still found in 5 districts, namely Purworejo, Banjarnegara, Purbalingga, Banyumas and Kebumen. Banjarnegara is one of the district in Central Java which is an  endemic area of malaria, the patients as many  247, of that 102 patients in Puskesmas Banjarmangu I,  Banjarmangu. This study aims to related factors attitude and behavior to the malaria. Method: The research was observasional analytic with case control design. The sample  of 34 cases and 34 controls,  with simple random sampling. Attitudes and behaviors were examined using logistic regression. Results: The result of study showed that attitude (p = 0,015; OR = 3,656; 95% CI = 1,292-10,344) and behavior (p = 0,031; OR = 2,962; 95% CI = 1,104-7,942) were significance relationship with malaria. Conclusion: Attitude and behavior related to the malaria in working area of Banjarmangu I, Banjarnegara. The  dominant factors was attitude.